Fetal epicardial fat thickness in diabetic and non‐diabetic pregnancies: A retrospective cross‐sectional study. (6th December 2015) - Jackson, Daniel; Deschamps, David; Myers, Dean; Fields, David; Knudtson, Eric; Gunatilake, Ravindu
Abstract : Objective: To evaluate fetal epicardial fat thickness (EFT) in diabetic and control pregnancies. Methods: A retrospective cross‐sectional study was performed in which fetal EFT was measured in the second trimester in 28 diabetics and 28 non‐diabetic patients. Maternal BMI, estimated fetal weight, birth weight, fetal abdominal circumference, and subcutaneous fat thickness were also collected. Statistical analysis was carried out by means of chi‐square, Wilcoxon rank‐sum test, Student's T test, and linear regression as appropriate. Results: EFT was significantly higher in diabetic (1.43 mm) vs. control fetuses (1.16 mm), P = 0.02. This relationship remained significant when controlling for covariates. Conclusions: EFT was higher in fetuses of diabetic mothers vs. fetuses from controls. If confirmed in prospective studies, this may represent a novel marker for altered fetal metabolism due to maternal diabetes.